2022
DOI: 10.1111/itor.13222
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear time‐series forecasts for decision support: short‐term demand for ICU beds in Santiago, Chile, during the 2021 COVID‐19 pandemic

Abstract: In Chile, due to the explosive increase of new COVID-19 cases during the first part of 2021, the ability of health services to accommodate new incoming cases was jeopardized. It has become necessary to be able to manage intensive care unit (ICU) capacity, and for this purpose, monitoring both the evolution of new cases and the demand of ICU beds, has become urgent. This paper presents short-term forecast models for the number of new cases and the number of COVID-19 patients admitted to ICUs in the Metropolitan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This section presents an overview of nine major global pandemic problem domains that analysts employ DES and ABS techniques to tackle (Hazarika and Gupta, 2020;He et al, 2020;Shim et al, 2020;Burgos and Ivanov, 2021;Akpan et al, 2023;Kim and Koo, 2021). The problems addressed using DES and ABS methods, as presented in Table 6, include epidemiological modeling, which involves forecasting COVID-19 infection and fatality rates (Hazarika and Gupta, 2020;Quiroga et al, 2021). Other pandemic challenges addressed involved evaluating the effectiveness of public health measures, contact tracing, and determining the optimal period for isolation.…”
Section: A Comparative Analysis Of Covid-19 Problems Tackled Using De...mentioning
confidence: 99%
See 2 more Smart Citations
“…This section presents an overview of nine major global pandemic problem domains that analysts employ DES and ABS techniques to tackle (Hazarika and Gupta, 2020;He et al, 2020;Shim et al, 2020;Burgos and Ivanov, 2021;Akpan et al, 2023;Kim and Koo, 2021). The problems addressed using DES and ABS methods, as presented in Table 6, include epidemiological modeling, which involves forecasting COVID-19 infection and fatality rates (Hazarika and Gupta, 2020;Quiroga et al, 2021). Other pandemic challenges addressed involved evaluating the effectiveness of public health measures, contact tracing, and determining the optimal period for isolation.…”
Section: A Comparative Analysis Of Covid-19 Problems Tackled Using De...mentioning
confidence: 99%
“…Scientists scrambled for quick practical solutions to stem the tide. OR and MS techniques, including modeling and simulation, provided potent strategies to forecast and initiate infection control initiatives (Quiroga et al., 2021). The global pandemic problems offer an opportunity to examine the discourse about the relevance and potency of DES as an OR method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, delayed discharge decisions may trickle down to emergency department admission delays, which are crucial for patient satisfaction (García‐Alfranca et al, 2018). Moreover, delays in emergency department admission may lead to emergency department crowding (Quiroga et al, 2022), which has been shown to further decrease patient satisfaction (Pines et al, 2008). Patient satisfaction is an important determinant of hospital revenue under the Value‐Based Purchasing program (Guadagnino, 2012).…”
Section: Countermeasures Against Externality From Economically Attrac...mentioning
confidence: 99%
“…Twitter data have been analyzed to understand the population-level spread of disease [ 29 - 31 ]. Furthermore, forecasting models have been created to track demand for ICU capacity planning in countries such as Chile [ 32 , 33 ], Brazil [ 34 ], Colombia [ 35 ], the United States [ 36 ], India [ 37 ], and China [ 38 ]. Previous studies have applied convergent cross-mapping (CCM) analysis to explore possible relationships involving antiepidemic measure–related tweets [ 39 ], the dynamics of misleading news on Twitter [ 40 ], and the identification of the global drivers of influenza [ 41 ].…”
Section: Introductionmentioning
confidence: 99%